An Assessment of fraud risk management and financial sustainability of Non - Governmental Organizations in Kenya - Kariuki, Mary (Strathmore University, 2017)
Fraud risk management practices influence the financial performance hence sustainability of Non-Governmental Organization. Several fraud risk management techniques are deployed within organizations to curb the vice. They include anti-fraud policies, management style, fraud detection and deterrence mechanisms and internal controls. This study seeks to establish relationship between fraud risk management and financial sustainability of non-governmental organizations in Kenya. The main variables of the study include the techniques of fraud risk used within NGOs in Kenya, extent of adoption of these techniques and relationship between fraud risk and financial sustainability within Kenyan NGOs. The study used an explanatory research design. The study collected both quantitative and qualitative data and analyzed it using content analysis, descriptive and correlational analysis methods respectively. The study revealed that fraud is an issue of concern among NGOs in Kenya as most of the NGOs conduct daily or weekly monitoring and apply anti-fraud teclmiques to a great extent while seeking to curb fraud. The findings indicated that the sector is financially sustainable with the large Organisations being more financially stable as compared to small organizations. A multiple regression model was also applied in deriving the relation between the dependent and independent variables. From the findings, the study concluded that all the independent variables; anti-fraud policies, fraud detection, fraud deterrence, internal controls and management style positively correlate with financial sustainability and have a statistically significant relationship with financial sustainability. These variables explain up to 73.1 percent of financial sustainability in Kenyan NGOs. The study recommends that anti-fraud policies should give clear guidance to employees, the organizations should establish policies around whistle blowing, monitoring and financial rep01iing processes should be considered while setting internal controls and that management should keenly support strategies towards fraud risk management. The outcome of the research will be beneficial in enhancing the understanding of fraud risk management specifically the aspects such as anti-fraud policies, fraud detection, fraud deterrence, internal controls and management style and their relationship to financial sustainability within the NGOs. The findings will also provide the management of NGOs with insight into the various approaches towards fraud risk management techniques and how effectively risk management techniques are in mitigating risks and influence financial performance and also contribute towards the establishment of the fraud triangle, self-control, differential association and fraud scale theories.
Submitted in partial fulfillment of the requirements for Degree of Master of Commerce of Strathmore University
Keywords: Fraud risk management; Financial sustainability; Non - Governmental Organizations